2005
DOI: 10.1191/1078155205jp155oa
|View full text |Cite
|
Sign up to set email alerts
|

Are health care providers who work with cancer drugs at an increased risk for toxic events? A systematic review and meta-analysis of the literature

Abstract: The results of this systematic review identified a small incremental risk for spontaneous abortions in female staff working with cytotoxic agents. Health policy decision makers should effectively communicate the magnitude of this risk to their staff and implement cost effective interventions for its reduction or elimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 28 publications
2
74
0
5
Order By: Relevance
“…A meta-analysis pooled the results of five studies 19-21, 24, 25 and found an overall adjusted increased risk of 46% (95% CI = 11%-92%). 28 Only one of these studies 25 occurred after safe handling measures were first recommended in 1985. 29,30 However, since 1985, several exposure studies still report drug contamination on work surfaces in pharmacies and patient rooms.…”
Section: Commentmentioning
confidence: 99%
“…A meta-analysis pooled the results of five studies 19-21, 24, 25 and found an overall adjusted increased risk of 46% (95% CI = 11%-92%). 28 Only one of these studies 25 occurred after safe handling measures were first recommended in 1985. 29,30 However, since 1985, several exposure studies still report drug contamination on work surfaces in pharmacies and patient rooms.…”
Section: Commentmentioning
confidence: 99%
“…1 Over the past 4 decades, there have been considerable advances in understanding the health outcomes associated with occupational exposure to antineoplastic drugs, including acute effects, 2,3 reproductive toxicities, [4][5][6] and carcinogenic potential. 5,7 Recent evidence has confirmed that a range of Canadian health care workers are at risk of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The effects have occurred at lower doses as compared to those administered to patients [55]. A meta-analysis reported increase in the rate of spontaneous abortions but not that of congenital malformations and still births [57]. Children of nurses handling chemotherapeutic drugs for a long period showed learning disabilities in another study [58].…”
Section: Hazards Of Exposure To Cytotoxic Agentsmentioning
confidence: 99%